Amniotic Membrane Origin, Characterization and Medical Applications - Mamede, Ana Catarina; Botelho, Maria Filomena; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2015)
This book describes the human amniotic membrane from its origin, characterization and medical applications, summarizing all the latest developments and findings related to this tissue with contributions from some of the leading researchers in the field. The book addresses issues for its preservation, separation and identification of amniotic membrane-derived cells, as well as the potential ethical issues involved in their use. The topic of this book is particularly pertinent for clinicians and researchers involved in the research and use of this tissue.
1 Embryology and anatomy of placental membranes -- 2 Biochemical properties of amniotic membrane -- 3 Biophysical properties of amniotic membrane -- 4 Stem properties of amniotic membrane-derived cells -- 5 Amniotic membrane in health and disease: an obstetrical perspect -- 6 Amniotic membrane in ophthalmology -- 7 Amniotic membrane in the treatment of burns -- 8 Amniotic membrane in cancer -- 9 Amniotic membrane in oral medicine -- 10 Amniotic membrane in gynaecology -- 11 Amniotic membrane and the controlled drug release -- 12 Isolation and characterization of mesenchymal stem cells from amniotic membrane -- 13 Preservation of amniotic membrane -- 14 Ethical and legal concerns of the use of amniotic membrane -- Index.
Keywords: Medicine; Medical biochemistry; Cell membranes; Biomedicine; Biomedicine general; Membrane Biology; Medical Biochemistry; Electronic books